Changes in key traits versus depth and latitude suggest energy‐efficient locomotion, opportunistic feeding and light lead to adaptive morphologies of marine fishes. Issue 2 (12th December 2019) - Myers, Elisabeth M. V.; Anderson, Marti J.; Eme, David; Liggins, Libby; Roberts, Clive D.
Abstract: Understanding patterns and processes governing biodiversity along broad‐scale environmental gradients, such as depth or latitude, requires an assessment of not just taxonomic richness, but also morphological and functional traits of organisms. Studies of traits can help to identify major selective forces acting on morphology. Currently, little is known regarding patterns of variation in the traits of fishes at broad spatial scales. The aims of this study were (a) to identify a suite of key traits in marine fishes that would allow assessment of morphological variability across broad‐scale depth (50–1200 m) and latitudinal (29.15–50.91°S) gradients, and (b) to characterize patterns in these traits across depth and latitude for 144 species of ray‐finned fishes in New Zealand waters. Here, we describe three new morphological traits, namely fin‐base‐to‐perimeter ratio, jaw‐length‐to‐mouth‐width ratio, and pectoral‐fin‐base‐to‐body‐depth ratio. Four other morphological traits essential for locomotion and food acquisition that are commonly measured in fishes were also included in the study. Spatial ecological distributions of individual fish species were characterized in response to a standardized replicated sampling design, and morphological measurements were obtained for each species from preserved museum specimens. With increasing depth, fishes, on average, became larger and more elongate, with higher fin‐base‐to‐perimeter ratio and larger jaw‐length‐to‐mouth‐width ratio, all of which translates into a more eel‐like anguilliform morphology. Variation in mean trait values along the depth gradient was stronger at lower latitudes for fin‐base‐to‐perimeter ratio, elongation and total body length. Average eye size peaked at intermediate depths (500–700 m) and increased with increasing latitude at 700 m. These findings suggest that, in increasingly extreme environments, fish morphology shifts towards a body shape that favours an energy‐efficient undulatory swimming style and an increase in jaw‐length vs. mouth width for opportunistic feeding. Furthermore, increases in eye size with both depth and latitude indicate that changes in both the average ambient light conditions as well as seasonal variations in day‐length can act to select ecomorphological adaptations in fishes. Abstract : The authors describe the variation of novel morphological traits for marine ray‐finned fishes across large‐scale depth and latitudinal gradients. Their findings suggest that, in increasingly extreme environments, body shape changes in favour of an energy‐efficient undulatory swimming style and an increase in jaw‐length vs. mouth‐width that enables more opportunistic feeding.